Glass Transition, Dynamics and Heterogeneity of Polymer Thin Films - Kanaya, Toshiji (Advances in Polymer Science, 2013)
Y. FujiiH. Morita A. Takahara K. Tanaka Mobility Gradient of Polystyrene in Films Supported on Solid Substrates G. Reiter Probing Properties of Polymers in Thin Films Via Dewetting K. Fukao T. Terasawa K. Nakamura D. Tahara Heterogeneous and Aging Dynamics in Single and Stacked Thin Polymer Films R. Inoue T. Kanaya Heterogeneous Dynamics of Polymer Thin Films as Studied by Neutron Scattering.